Axodendritic targeting of TAU and MAP2 and microtubule polarization in iPSC-derived versus SH-SY5Y-derived human neurons - Breuer Helen; Bell-Simons Michael; Zempel Hans (Open Life Sciences)
Cell polarity is crucial in neurons, characterized by distinct axonal and dendritic structures. Neurons generally have one long axon and multiple shorter dendrites, marked by specific microtubule (MT)-associated proteins, e.g., MAP2 for dendrites and TAU for axons, while the scaffolding proteins AnkG and TRIM46 mark the axon-initial-segment. In tauopathies, such as Alzheimer’s disease (AD), TAU sorting, and neuronal polarity are disrupted, leading to MT loss. However, modeling and studying MTs in human neuronal cells relevant to the study of AD and TAU-related neurodegenerative diseases (NDD) is challenging. To study MT dynamics in human neurons, we compared two cell culture systems: SH-SY5Y-derived neurons (SHN) and induced pluripotent stem cell-derived neurons (iN). Using immunostaining and EB3-tdTomato time-lapse imaging, we found AnkG absent in SHN but present in iN, while TRIM46 was present in both. TAU and MAP2 showed axonal and dendritic enrichment, respectively, similar to mouse primary neurons. Both neuron types exhibited polarized MT structures, with unidirectional MTs in axons and bidirectional MTs in dendrites. Polymerization speeds were similar; however, iNs had more retrograde MT growth events, while SHN showed a higher overall number of growth events. Thus, SHN and iN are both suitable for studying neuronal cell polarity, with SHN being particularly suitable if the focus is not the AIS.